EMOTIONAL INTELLIGENCE AS A PREDICTOR OF ACADEMIC ACHIEVEMENT ACROSS BOARD AND GENDER OF HIGHER SECONDARY SCHOOL STUDENTS - Mandloi, Shilpa; R P Pandey (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional intelligence cultivates essential abilities such as emotional regulation, personal goal setting, optimism, self-awareness, flexibility, adaptability, and problem-solving in both personal and interpersonal contexts. These competencies play a pivotal role in fostering holistic development and enhancing academic performance. The present study examines the relationship between academic achievement and emotional intelligence, with a specific focus on the influence of the school board (CBSE vs. State Board) and gender. Data were collected using the Dr. S.K. Mangal and Shubhra Mangal Emotional Intelligence Inventory, a standardized tool consisting of 100 items. The sample comprised 160 students (80 males and 80 females) randomly selected from two CBSE and two State Board higher secondary schools in Mandsaur District, Madhya Pradesh. For statistical analysis, Pearson Correlation Coefficient and Multiple Linear Regression Analysis were employed to determine the significance of the relationship between emotional intelligence and academic achievement across the identified variables. The Pearson correlation results indicated a moderate positive correlation between emotional intelligence and academic achievement, with CBSE higher secondary students exhibiting a stronger positive correlation compared to their State Board counterparts. Additionally, male students demonstrated a higher correlation between emotional intelligence and academic performance than female students. Multiple Regression Analysis further revealed that emotional intelligence significantly influences academic achievement, with school board type (CBSE or State) and gender serving as contributing factors. The findings suggest that emotional intelligence plays a crucial role in shaping academic success, with CBSE students and male participants displaying relatively stronger relationships between these variables. This study underscores the importance of emotional intelligence in preparing students for future challenges, fostering holistic development, self-reflection, and adaptive learning strategies. It highlights the need for integrating innovative teaching methodologies that enhance emotional growth and, consequently, academic performance.